A Retrospective Study of Erythema Nodosum Leprosum in Dermatology and Venereology Outpatient Clinic of Sanglah General Hospital, Bali-Indonesia - I Gusti Nyoman Darmaputra (Journal of Global Pharma Technology, 2019)
Introduction: Erythema nodosum leprosum (ENL) or type II reaction in leprosy is acute inflammation in the chronic disease of multibacillary leprosy. Clinical manifestation of ENL on the skin such as painful cutaneous nodule, commonly found on the face and extremities accompanied by nerve inflammation, systemic involvement, and other extracutaneous symptoms which possibly caused disability if it is not treated appropriately. Aim: To find out the ENL pattern in the Department of Skin and Venereology, Sanglah General Hospital for three years. Methods: This study was a retrospective study from the medical record of ENL new cases treated in the Skin and Venereology Outpatient Clinic, within period January 2013-December 2015 classified by the number of patients, age, sex, and type of leprosy. Result: Starting from January 2013-December 2015 there were about 39 new leprosy patients with ENL (36% of all new patients in the leprosy division), 64% are male, 82% aged 17-45 years, and 69% of patients suffer from borderline lepromatous (BL) leprosy. Conclusion: Most leprosy patients with ENL are male, aged 17-45 years with BL type leprosy. Complications that arise due to ENL or the side effects of corticosteroids could cause a large socio-economic impact.Keywords: Erythema nodosum leprosum, Leprosy reaction, Sanglah General Hospital.